2010
DOI: 10.1007/s00246-009-9626-8
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Dimensions in Girls and Young Women with Turner Syndrome: A Magnetic Resonance Imaging Study

Abstract: This study aimed to determine the dimensions of the thoracic aorta and the predictors of aortic dimensions in girls and young women with Turner syndrome (TS). A cross-sectional study was performed at a secondary care center. The study compared 41 TS patients with 50 healthy age-matched control subjects. The mean age of the patients was 17 +/- 3.3 years. Magnetic resonance imaging was performed for all the patients. The thoracic aortic diameters of the patients were measured at nine positions. Adjustment for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 27 publications
3
29
1
Order By: Relevance
“…This is to be interpreted as PWVf, AIx, and YEM being representative of functional changes, which may precede the structural changes of arterial thickness (cIMT). Because our patients were 10 -30 years younger than adult TS patients previously studied (1,8,27,28), and because they had not been subjected to pro- longed environmental exposures commonly associated with atherosclerosis, our data may very well indicate that these functional changes (ie, increased vascular stiffness) could represent an important early marker of vasculopathy entirely inherent to the TS phenotype. These functional changes may be occurring before any structural damage is seen with increasing chronological age.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is to be interpreted as PWVf, AIx, and YEM being representative of functional changes, which may precede the structural changes of arterial thickness (cIMT). Because our patients were 10 -30 years younger than adult TS patients previously studied (1,8,27,28), and because they had not been subjected to pro- longed environmental exposures commonly associated with atherosclerosis, our data may very well indicate that these functional changes (ie, increased vascular stiffness) could represent an important early marker of vasculopathy entirely inherent to the TS phenotype. These functional changes may be occurring before any structural damage is seen with increasing chronological age.…”
Section: Discussionmentioning
confidence: 90%
“…Studies evaluating the presence of vasculopathy in the adult TS population have identified vascular changes as early as the third decade of life (1,5,8), and…”
Section: Design and Patientsmentioning
confidence: 99%
“…The entire thoracic aorta is at risk of dilation and dissection in TS [7,11]. The present study utilised a dynamic and integrative approach to both baseline CMR data and to the longest registered prospective characterisation of aortic diameter of the entire thoracic aorta in TS.…”
Section: Discussionmentioning
confidence: 99%
“…Histological evidence of cystic medial necrosis has been reported in Turner syndrome. The prevalence of aortic dilation and aneurysm is lower in the young girls and women with Turner syndrome than in older Turner syndrome population [39,40].…”
Section: Turner Syndromementioning
confidence: 90%